Developing patient reported outcome measures for children with cancer: A current perspective - Madeleine Adams; Rachel M. Taylor (EJC Paediatric Oncology, 2025)
Patient reported outcomes measures (PROM) are the gold standard for evaluating patient experience and quality of life (QOL), both in research studies and clinical practice. In paediatric oncology, the wide spectrum of disease and treatment strategies means that correct choice of PROM and robust methodology when developing new PROMs is vital to ensuring that the desired outcomes (e.g. pain, functional ability or quality of life) are accurately assessed. Children differ from adults both medically and developmentally meaning that specific factors should be considered including age and developmental ability, use of proxy/observer reports and mode of administration. Best practice guidelines outline the methodology for developing the content of a new PROM as well as assessing psychometric properties. This paper provides a review of the background, current guidelines, and methodology for developing and choosing PROMs for children with cancer.